Translation Issues in the Translation Process of “Pirates of the Caribbean; the Curse of the Black Pearl” Movie Script - Gandung Aulia Wiratmoko (Jurnal Smart Hukum (JSH), 2023)
This research article aimed to classify the types of issues and its translation strategies in Pirates of the Caribbean; The Curse of the Black Pearl. The descriptive qualitative paper using content analysis and documentation in collecting the data. All data were analysed by identifying and determining the translation strategy of idiom, slang, jargon and cultural term. The results showed that the frequency of idiom is 26, the number of jargon is 18, the number of slang is 14 and cultural term is that occured in the movie script. The issues are in the form of Idiom, Jargon, Slang and Cultural Term. Idiom were analyzed by four strategies for translating idiom. Jargon were analyzing by understanding the term and the context. And slang were analyzed by the term and the use.